1999
DOI: 10.1007/pl00011758
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Diversity in Three Populations of the Giant Tiger Shrimp Penaeus monodon

Abstract: : Mitochondrial DNA restriction fragment length polymorphism (mtDNA-RFLP) was utilized for determination of genetic variation and population structure in Penaeus monodon collected from Satun (the Andaman Sea) and Surat and Trat (the Gulf of Thailand). Twenty-eight composite haplotypes were generated from 52 restriction profiles of P. monodon mtDNA digested with 11 restriction endonucleases. The size of the entire P. monodon mitochondrial genome was estimated to be 15.913 +/- 0.177 kb. The average haplotype div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
2
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 22 publications
(17 reference statements)
1
20
2
1
Order By: Relevance
“…The nucleotide diversity values (π) reported in this study are in the same range as those derived from mtDNA variation of tiger prawn (P. monodon) (Klinbunga et al 1999;Benzie et al 2002) (Kong et al 2010) populations; although Cui et al (2007), in contrast, reported relatively low haplotype diversity value (0.24) in P. chinensis. The nucleotide diversity observed in this study is interestingly close to the highest level of π observed for Penaeus monodon in Indonesia, which could be explained by migrations from the oceans to the east and west of the studied region (Benzie et al 2002).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The nucleotide diversity values (π) reported in this study are in the same range as those derived from mtDNA variation of tiger prawn (P. monodon) (Klinbunga et al 1999;Benzie et al 2002) (Kong et al 2010) populations; although Cui et al (2007), in contrast, reported relatively low haplotype diversity value (0.24) in P. chinensis. The nucleotide diversity observed in this study is interestingly close to the highest level of π observed for Penaeus monodon in Indonesia, which could be explained by migrations from the oceans to the east and west of the studied region (Benzie et al 2002).…”
Section: Discussionsupporting
confidence: 74%
“…The ecological and economic importance of these shrimps has led to much biological and genetic research. Penaeids show Supporting information is only available in electronic form at www.alr-journal.org a Corresponding author: dileepa_dc@yahoo.com a wide range of patterns of intraspecific population genetic structure: some researchers have reported the absence of distinguishable population structures over thousands of kilometers (Benzie 2000;Brooker et al 2000;McMillen-Jackson and Bert 2004a;Cui et al 2007), while others report significant structural differentiation over hundreds of kilometres (Klinbunga et al 1999;You et al 2008). According to Benzie (2000), most of the genetic structure observed in penaeids is due to historic events, and can be maintained by present-day barriers to gene flow (Aubert and Lightner 2000;Garcia-Machado et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial DNA (mtDNA) shows a high level of polymorphism and an evolutionary rate 10 times faster than nuclear genomes and is subject to maternal and asexual inheritance (Awadalla et al, 1999), characteristics which make mtDNA very useful for genetic studies in aquaculture (Allegrucci et al, 1998). Sequence analyses of mtDNA have been widely used in phylogenetic studies of natural shrimp populations (Bouchon et al, 1994;Baldwin et al, 1998;Klinbunga et al, 1999;Gusmão et al, 2000;Maggioni et al, 2001) and to evaluate genetic divergence between captive populations (Iguchi et al, 1999;Sekino et al, 2002). The 16S rRNA gene is found in the conserved portion of the mtDNA and has been extensively used in phylogenetic studies while the cytochrome oxidase I (COI) gene, which seems to be less conserved than the 16S rRNA gene, has been frequently used in evolutionary studies (Clary and Wolstenholme, 1985;Beard et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The geographic differentiation have been observed in Penaeid (Aubert and Lightner, 2000;De La Rosa -Velez et al, 2000;Gracia et al, 2001;Xu et al, 2001). Phylogeographical subdivision of genetically distinct varieties is not uncommon in Penaeus species such as Farfantepenaeus subtilis (Perez Farfante, 1967) in South America (Gusmao et al, 2000), F. merguiensis in Thailand (Hualkasin et al, 2003) and P. monodon in Thailand (Klinbunga et al, 1999;Supungul et al, 2000) and in the Indo west Pacific region Benzie et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Previously many genetic diversity studies using allozyme analysis has been used to determine the levels of variation and degree of genetic subdivision for several shrimp species (Lester and Pante, 1992;De la Rosa-Velez et al, 2000;Gracia-Machado et al, 2001;Gusmao et al, 2005), and mitochondrial DNA restriction fragment length polymorphism (Benzie et al, 1993;Klinbunga et al, 1999Klinbunga et al, , 2001Gracia-Machado et al, 2001). Genetic diversity and geographic differentiation of the P. monodon mitochondrial COI sequences (Kumar et al, 2007;Khamnamtong et al, 2009).…”
Section: Introductionmentioning
confidence: 99%